Planetary Health Diet Index and self-reported kidney stones in US adults: mediating role of high-density lipoprotein cholesterol - Yang, Qinglong; Chen, Haolin; Luo, Nan; Lin, Hanyuan; Tang, Haoxian; Huang, Jingtao; Zhang, Xuan; Liao, Wenqiang; Hou, Gaoming; Lin, Yuxue; Liu, Zexuan; Sui, Xuxia; et al. (Frontiers in Nutrition, 2025)
BackgroundKidney stone is a universal health concern, with its incidence influenced by dietary habits. The Planetary Health Diet (PHD) benefits human health and the environment.ObjectiveThis study aims to examine the relationship between the Planetary Health Diet Index (PHDI) and self-reported kidney stones and to explore the mediating role of high-density lipoprotein cholesterol (HDL-C).MethodsThis study included 19,249 participants (≥20 years old) from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Kidney stone diagnoses were self-reported. Higher PHDI scores represented greater compliance with the PHD. The statistical analyses encompassed a weighted multivariable logistic regression model, restricted cubic spline curve analysis, mediation analyses, subgroup analysis, and sensitivity analysis.ResultsIn the fully adjusted model, each 10-point rise in PHDI was tied to an 8% decrease in self-reported kidney stone risk (OR, 0.92; 95% CI, 0.87–0.97). Participants in the top quintile of PHDI had a 25% lower risk of self-reported kidney stones than those in the bottom quintile (OR, 0.75; 95% CI, 0.58–0.96). HDL-C mediated 6.0% of the correlation between PHDI and self-reported kidney stones.ConclusionPlanetary Health Diet Index reduced the risk of self-reported kidney stones, with HDL-C partially mediating this effect.